PENGARUH PENGEMBANGAN KARIR DAN KOMPENSASI TERHADAP TURNOVER INTENTION - Wati, Handarini Cinta; Ardiansyah, Fajar; Burhanudin, Burhanudin (Universitas Nusantara PGRI Kediri, 2023)
This study aims to: (1) examine the effect of career development on turnover intention; and (2) examine the effect of compensation on turnover intention. The population in this study were 123 employees of PT. Telkom Access Yogyakarta. The data collection technique used a questionnaire, while the data analysis technique used multiple linear regression. The research results found that career development had an influence on turnover intention and compensation had no influence on turnover intention.